The Future of Education Research Journals: Challenges and responses - David Post (Arizona State University, 2014)
This special issue of Education Policy Analysis Archives addresses scholarly production and publishing (the two are intimately related) in the field of education. Worldwide scholars are facing similar global pressures for "excellence" and where the personal and institutional production of excellent scholarship is being compared with simple measures.  In some parts of the world, these measures of productivity are fast becoming more immediately consequential than whatever else may be produced as a result of scholarship (purpose, critical reflection, insight, meaning, progress, to list some examples). This essay presents the challenges and responses identified by the eight contributions for this special issue on the future of education research publishing.  .